Aqueous Extract of the Root of Asparagus Racemosus as A Potential Anthelmintic Agent against Gastrointestinal Nematodes in Goats - Pandey, Arjun (NPRC Journal of Multidisciplinary Research, 2025)
Asparagus racemosus (AR) is a medicinal plant of Liliaceae family, traditionally used as treatment for helminths. The present study was aimed to investigate the anthelmintic activity of aqueous extract of AR root against gastrointestinal nematodes in goats. The extracts of AR root were prepared by boiling in distill water followed by filtration in Whatman No.1 filter paper. Then, phytochemical screening of the extract was done by using several qualitative tests. Altogether 40 male goats having EPG at least 100 were chosen for experiment after the screening of naturally infected flock by direct smear and faecal flotation method. Then, total 40 male goats were allocated equally randomly in AR-100, AR-200 and Positive control (P-Ctrl) and Negative control (N-Ctrl), groups. The goats of AR-100, AR-200 and P-Ctrl groups received oral administration of aqueous extract of AR root at a rate of 100 mg/kg, 200 mg/kg and albendazole 10 mg/kg, respectively. However, distilled water was provided to goats of N-Ctrl group.  The EPG was assessed by modified Mc-Master technique on day 0, 3, 7, 14, and 28. Also, FECR% were assessed on day 7, 14, 21 and 28. Data of EPG and FECR% were analyzed using One-Way ANOVA followed by LSD for multiple mean comparisons by using SPSS. Phytochemical screening on this extract showed the presence of phytosterol, saponin, carbohydrate and reducing sugar. The EPG was decreased in extract treated group on the dose dependent manner on day 7, 14, 21 and 28. The FECR% is higher on both extract treated group on day 7. However, FECR% on the extract treated group was increased on dose dependent manner on day 14, 21 and 28. The extract at the dose rate 100 mg/kg bwt and 200 mg/kg bwt showed the maximum FECR% 59.05±0.73 and 88.82±4.94 respectively on day 28. So, it is concluded that aqueous extract of root of Asparagus racemosus at dose rate 200 mg/kg bwt has sufficient anthelmintic activity against gastrointestinal nematodes in goat. Further research is imperative to separate the possible anthelmintic component and understand its mechanism of action, bioassay-guided fractionation should be utilized for further evaluation of bioactive component.